Penerapan Prinsip Fiduciary Duty Untuk Mewujudkan Good Corporate Governance Dalam Perseroan Terbatas - Arifin, Abiyyu Paras Syakir; Sodikin, Sodikin (Journal of Contemporary Law Studies, 2025)
This study examines the application of the fiduciary duty principle in realizing Good Corporate Governance (GCG) within Limited Liability Companies in Indonesia. Fiduciary duty serves as a fundamental principle requiring directors and commissioners to act in good faith, with loyalty and prudence, to safeguard the interests of the company and its stakeholders. This research employs a normative juridical approach by analyzing relevant legal frameworks, literature, and regulations, particularly Law Number 40 of 2007 concerning Limited Liability Companies. The findings indicate that effective implementation of fiduciary duty strengthens corporate accountability, transparency, and compliance with legal provisions, ultimately fostering a more ethical and sustainable business environment. However, challenges such as conflicts of interest, lack of transparency, and limited awareness among corporate executives hinder its full implementation. Therefore, continuous education and training for directors and management are essential to enhance their understanding of fiduciary responsibilities. Despite the study’s limitation in scope, which is primarily focused on the Indonesian legal framework, its findings provide valuable insights for improving corporate governance practices. Future research should explore fiduciary duty across various industries to develop more comprehensive recommendations. By consistently applying fiduciary duty principles, companies can achieve robust and accountable corporate governance, thereby supporting long-term corporate growth and sustainability.